Creating conference posters: Structure, form and content - Barker, Eleanor (J Perioper Pract, 2021)
This article aims to provide an overview of the form, structure and content of conference posters for researchers who intend to submit an academic poster to a conference. It focuses in particular on the design and layout of academic conference posters, making some suggestions for possible poster layouts. It also provides information about factors influencing conference selection. Finally, it summarises some top tips to be considered when creating a conference poster such as font selection and use of images.